Multiple Uterine Fibroids in an Young Adult - Shahina Ishtiaq; Darayus P. Gazder; Nabeel Khan (ziauddin University, 2024)
Uterine leiomyoma's are noncancerous growths of the uterus1 and represent the most common benign tumors of the female reproductive tract. Fibroids affect 20-50% of women of reproductive age, while its presence in the adolescent population has not been well documented. The etiology of uterine fibroids is unclear; however, their growth is regulated by ovarian steroids, and growth factors. Multiple uterine leiomyoma's represents a great challenge for diagnosis and therapy. Several new therapies show promise, but are still at the experimental stage.2 This report illustrates the case of a 22 year old woman presenting to the gynecology department with an 8-month history of progressively increasing abdominal size associated with pain. There was no history of nausea, vomiting, weight loss, loss of appetite or menstrual irregularities. Physical examination and ultrasound pelvis suggested multiple enlarged uterine fibroids. A myomectomy was performed and multiple fibroids were resected weighing 4.5kg. The patient's postoperative evolution was uneventful and she was discharged from the hospital on the fourth postoperative day. Key Words: Multiple Uterine Leiomyoma's, Myomectomy, Ovarian Steroids.